Allpamanda, Kawsaymanda, Jatarishun allampamanda muskuykuna tuparishka. Por la tierra, por la vida, despertemos confrontación entre visiones sobre el território. - Santi, Enoc Moisés Merino (2016)
In order to understand why the state denied the right to autonomy and management of territories according to the worldview of each indigenous nationality, which has been and continues to be a source of social conflict, I dove into the magical and diverse world of thoughts, representation and symbols that give meaning to the territory in the indigenous nationality of Ecuador, which in search of a territorial and cultural visibility has reconceptualized their forms of social intercourse and political organization. My investigation, study and analysis camp was the Kichwa nationality, so I went from the city to the jungle, Quito, Puyo and the Pakayaku Clanship, nationality "Kichwa Canelos" or "Kichwa Curaray" were my stops, where I did my fieldwork. This study was conducted between 2015 and 2016. Readings and discussions I had with indigenous leaders from Amazon and Highlands, indigenous students of the Amazon State University and coexistence held in the Pakayaku clanship in order to compare their social and territorial relationship in the contemporary helped me to complete this work. I attempt to discuss not a canonical scientific study with the traditional scheme of research, but, I bring to the stage a descriptive work of the historical process, construction of identity, visions of the territory, the organizational situation and political positioning of the Nationality under study, against his opponent the "National State”